An Econometric Analysis of the Impact of Climate Change on Wheat Yield in the Gangetic Indo-Plains of India : A Study of Meerut District - Saxena, Swami Prasad; Kumar, Anuj (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : The study aimed to examine how climate change is affecting wheat crop yields in Meerut, a significant wheat-producing district in India’s Indo-Gangetic Plain (IGP) region. Methodology : The OLS technique was applied to annual data covering 40 years, from 1980 to 2020, in order to investigate the effects of variations in meteorological variables, specifically mean temperature, maximum temperature, minimum temperature, and rainfall, on wheat yield. Findings : The results of OLS estimation indicated that around 61% of changes in wheat yield are governed by climatic factors. The results revealed that the average mean temperature was good for wheat crops in the second (growth) stage. In the final stage, which is before harvesting, the highest temperature reduces wheat output. In the past 10 years, it has also been noted that lower minimum temperatures and higher maximum temperatures during the initial stages of the crop had a negative impact on wheat output. Rainfall timing, which is crucial for the wheat crop, is changing in the area; it was occurring after the wheat was torn, which had a detrimental effect on wheat output. Practical Implications : The output of wheat harvested in the Meerut district is being adversely affected by climate change. To maintain the crop, the government and farmers need to work together to implement various adaptation strategies. Originality : There was a paucity of research work at the district level in the current domain of research. This paper tried to bridge the gap in the literature, focusing primarily on the study of the impact of climate change on wheat yield in Meerut, a district of the IGPs region of India.